Resale Price Maintenance in a Successive Monopoly Model - Markus Dertwinkel-Kalt; Christian Wey (The Journal of Industrial Economics, 2023)
We explain why a manufacturer may impose a minimum resale price in a successive monopoly setting. Our argument relies on the retailer having noncontractible choice variables such as the price of a substitute good and/or the retailer's service effort. Our explanation for minimum resale prices is empirically distinguishable from alternative justifications that rely, for instance, on retailer competition and service free riding among retailers. Whether a min RPM benefits or harms consumers depends on its effects: if it softens competition with the substitute product, it tends to harm consumers, and if it secures service provision, it tends to benefit consumers.
Keywords: 330